Aesthetic Gingival Recontouring - Bajracharya, Alina; Shrestha, Surendra Man; Pradhan, Ameena; Aryal, Shreeya; Shrestha, Shilu (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
The dramatic appeal of a face, especially caught in a smile or laugh, lies in the interplay between the lips, teeth, and periodontium. Any deviation from the ideal form alters perceived attractiveness. Excessive marginal or papillary soft tissue because of inflammation, altered passive eruption, and a myriad of other pathologies distorts dental silhouettes. Modification of the gingiva, then, instead of tooth structure, often resolves cosmetic deformities. In this case report, we discuss about aesthetic crown lengthening, that aims to reduce excessive soft and hard tissues to establish a natural smile with harmonious proportion between the teeth and the dentogingival complex.